PPARγ Interaction with UBR5/ATMIN Promotes DNA Repair to Maintain Endothelial Homeostasis - Li, Caiyun G.; Mahon, Cathal; Sweeney, Nathaly M.; Verschueren, Erik; Kantamani, Vivek; Li, Dan; Hennigs, Jan K.; Marciano, David P.; Diebold, Isabel; Abu-Halawa, Ossama; Elliott, Matthew; Sa, Silin; et al. (Cell reports (Cambridge), 2019)
Using proteomic approaches, we uncovered a DNA damage response (DDR) function for peroxisome proliferator activated receptor γ (PPARγ) through its interaction with the DNA damage sensor MRE11-RAD50-NBS1 (MRN) and the E3 ubiquitin ligase UBR5. We show that PPARγ promotes ATM signaling and is essential for UBR5 activity targeting ATM interactor (ATMIN). PPARγ depletion increases ATMIN protein independent of transcription and suppresses DDR-induced ATM signaling. Blocking ATMIN in this context restores ATM activation and DNA repair. We illustrate the physiological relevance of PPARγ DDR functions by using pulmonary arterial hypertension (PAH) as a model that has impaired PPARγ signaling related to endothelial cell (EC) dysfunction and unresolved DNA damage. In pulmonary arterial ECs (PAECs) from PAH patients, we observed disrupted PPARγ-UBR5 interaction, heightened ATMIN expression, and DNA lesions. Blocking ATMIN in PAH PAEC restores ATM activation. Thus, impaired PPARγ DDR functions may explain the genomic instability and loss of endothelial homeostasis in PAH. [Display omitted] •PPARγ proteomics identifies interactions with the MRE11-RAD50-NBS1 complex and UBR5•Upon DNA damage, PPARγ promotes UBR5-mediated ATMIN degradation to activate ATM•PPARγ-UBR5 interaction is disrupted in endothelial cells isolated from PAH patients•Depleting ATMIN in PAH endothelial cells restores ATM signaling upon DNA damage Li et al. identify PPARγ interactions with MRN and UBR5. PPARγ promotes UBR5-mediated ATMIN degradation, necessary for ATM activation upon DNA damage. Pulmonary arterial hypertension (PAH) endothelial cells exhibit genomic instability and disrupted PPARγ-UBR5 interaction. Blocking ATMIN restores ATM signaling in these cells, highlighting the significance of the PPARγ-ATMIN axis.